Green Governance: The Role of Public Administration in Achieving the Sustainable Development Goals - Giri, Prem Bahadur; Dhakal, Tek Nath; Ghimire, Hari Prasad; Giri, Uttam Raj; Giri, Ajay (NPRC Journal of Multidisciplinary Research, 2026)
Background: Green governance endorses the Sustainable Development Goals, but the administrative processes under which sustainability is structured by the public institutions are little known. Current literature is predominantly set on environmental policy instruments, and little has been said on the role that the public administration plays as a governance player in determining policy consistency and outcomes. Methods: The paper will use PRISMA 2020 to conduct a systematic literature review. The Scopus, Web of Science, and Google Scholar retrieved articles published after 2020. There were 53 studies identified in the multi-stage screening process. The thematic synthesis was used to analyze the selected literature to determine common patterns of governance, institutional mechanisms, and administrative challenges. Results: According to the review, there are five fundamental dimensions. Mechanisms of governance, bureaucratic capacity and policy tools, institutional barriers and best practices. Comprehensive and inclusive systems of governance enhance the coherence and legitimacy of policies. Regulatory and adaptive capacity is optimized by professional and independent bureaucracies. Sustainability performance is enhanced with combined regulatory, market-based, and informational tools. The operational environment of fragmented institutions, low capacity, low accountability and political short-termism still limits the implementation of SDGs. Conclusion: Green governance also requires institutional quality and administrative capacity rather than policy design. Sustainability commitments need to be converted into practical results, which require strong coordination, participation and performance monitoring. Novelty: The paper reconstructs the concept of green governance as an administrative transformation process and places a central role in sustainability transitions as a constitutive agent of the public administration.